Low hemoglobin levels are associated with reduced psychomotor and language abilities in young Ugandan children - Nampijja, M; Mutua, AM; Elliott, AM; Muriuki, JM; Abubakar, A; Webb, EL; Atkinson, SH (MDPI, 2022)
Children living in Sub-Saharan Africa are vulnerable to developmental delay, particularly in the critical first five years due to various adverse exposures including disease and nutritional deficiencies. Anemia and iron deficiency (ID) are highly prevalent in pregnant mothers and young children and are implicated in abnormal brain development. However, available evidence on the association between anemia, ID and neurodevelopment in sub-Saharan Africa is limited. Using data from the Entebbe Mother and Baby Study prospective birth cohort, we examined the effect of maternal and child hemoglobin (Hb) levels and child iron status on developmental scores in 933 and 530 pre-school Ugandan children respectively. Associations between Hb levels, iron status and developmental scores were assessed using regression analyses adjusting for potential confounders. Lower maternal and child Hb levels were associated with reduced psychomotor scores at 15 months, while only lower Hb levels in infancy were associated with reduced language scores. We found no evidence that anemia or ID was associated with cognitive or motor scores at five years. This study emphasizes the importance of managing anemia in pregnancy and infancy and highlights the need for further studies on the effects of anemia and ID in children living in Sub-Saharan Africa.